Explanation: Just addition and subtraction which is easy, I'd remove the brackets first so it won't be too confusing.
[tex]9c-8d+2c-6-d+3=???[/tex]
Here, just remember that:
Notice the +(-d+3), (+)(-) = - so it's -d+3
Now just addition and subtraction, for better looking and non-confusing.
[tex]9c+2c-8d-d-6+3=???\\9c+2c-8d-d-6+3=11c-9d-3[/tex]
9c+2c = 11c
-8d-d = -9d
-6+3 = -3
Therefore, the answer is [tex]11c-9d-3[/tex]
If you are confused, you can reply to this explanation (If it's wrong, let me know.)